Non-tropical pyomyositis. Issue 10 (October 1986) - Muscat, I; Anthony, P P; Cruickshank, J G
Abstract : Pyomyositis occurred in a man who had not been to the tropics. The condition is common in the tropics but most unusual in temperate climates and is nearly always caused by Staphylococcus aureus. Pyomyositis must be borne in mind in obscure cases of sepsis, as early recognition and treatment are essential to prevent a fatal outcome.